Memórias de uma professora - SOARES, Selma Lúcia da Silva (2019)
This work results from a memorial, which brings the life story in the form of narration. These are memories that mean lived moments that run through my childhood, through academic life to teaching. As a goal I tried to remember my life story and teacher, with the intention of reconstructing the narratives immersed in the events and experiences of education, which contributed as a teacher in elementary school. Aware of this, the memorial presents itself at crucial moments in a timeline, where it is scientifically supported by critics and theorists who address the concepts memory, history and teacher education in a focus of readings and reflections, such as Bragança (2012), António Nóvoa. (1992), (1999), Le Goff (1990), Mignot (2003), Bondia (2002) and Candau (2012). In this memorial I used the methodology of life history, followed by interviews of people who certainly were part of moments that stood out in my timeline, and can count on the support of my father, sister and aunt to report the facts that occurred in this path of life. Finally, I come to the conclusion that about this wonderful journey into the past, all the writing in this work is based on a theoretical sequence.